364 IMPACT ON SURGICAL AND ONCOLOGIC OUTCOMES OF NEOADJUVANT CHEMOTHERAPY VERSUS SURGERY ALONE IN ELDERLY PATIENTS WITH LOCALLY INVASIVE GASTROESOPHAGEAL CANCER. (14th September 2020) - Antoun, A; Kammili, A; Naghawi, H; Alcindor, T; Asselah, J; Vanhuyse, M; Cools-Lartigue, J; Ferri, L; Mueller, C
Abstract: : Neoadjuvant chemotherapy (nCT) has an increasingly important role in the treatment of locally invasive gastric and esophageal adenocarcinoma. However, its outcomes have not been examined in cohorts of exclusively elderly patients who may not experience the same benefits as younger patients and are more vulnerable to adverse events from the treatment. The purpose of this study is to determine the impact of nCT on outcomes among elderly patients with gastric and gastroesophageal adenocarcinoma. Methods: All patients who underwent curative-intent surgery for gastric and gastroesophageal adenocarcinoma between 2010 and 2018 at a high-volume multidisciplinary referral center were identified from a prospectively collected database. Early stage tumours at diagnosis (T1N0 or T2N0) and emergency resections were excluded. Patient characteristics, surgical outcomes and oncologic outcomes were verified by chart review and death dates verified using provincial registry data. Comparison was made for all variables between patients who were treated with nCT and those who were treated with surgery alone (SA). Subgroup analysis among patients aged 70+ was conducted to determine differences in outcomes among elderly patients. Results: Of 766 cases in the database, 354 met inclusion criteria (SA: 99 vs nCT: 255). Of those who received nCT, 77 (30.3%) were ≥ 70 years of age. When compared to younger patients, this cohort experienced significantly more high-grade toxicity from chemotherapy (<70: 32 (18.1%); 70+: 25 (32.5%); p = 0.017), but completion rates and timely progression to surgery were similar between groups (Table 1). Multivariate analysis among elderly patients showed that patients who had nCT had similar overall survival (HR 1.04, 95% CI 0.35-1.19) and disease-free survival (HR 1.04, 95% CI 0.41-1.36) to those who were treated with SA. Conclusion: Neoadjuvant chemotherapy administered to elderly patients with locally advanced gastroesophaeal adenocarcinoma results in higher rates of high-grade toxicity with no difference in long term oncologic outcomes when compared to surgery alone. Consideration should be given to upfront surgery for elderly patients with resectable gastric and gastroesophageal tumours at presentation.